2002
DOI: 10.1007/s00432-002-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the 27-kDa heat shock protein (HSP27) in gastric carcinomas and adjacent normal, metaplastic, and dysplastic gastric mucosa, and its prognostic significance

Abstract: Our findings indicate that: i) HSP27 is commonly expressed in normal gastric epithelium where it seems to exert a protective role; and ii) HSP27 is involved in gastric carcinogenesis and its expression appears to be associated with parameters of unfavorable prognosis and shorter overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…In contrast, HSP27 expression has been reported to have no effect on prognosis in head and neck squamous cell carcinoma [46], bladder cancer [47] or renal cell carcinoma [48]. Data are inconclusive in oral squamous cell carcinoma [49-52], gastric cancer [53-55] and ovarian cancer [56-61]. Studies in pancreatic cancer were still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HSP27 expression has been reported to have no effect on prognosis in head and neck squamous cell carcinoma [46], bladder cancer [47] or renal cell carcinoma [48]. Data are inconclusive in oral squamous cell carcinoma [49-52], gastric cancer [53-55] and ovarian cancer [56-61]. Studies in pancreatic cancer were still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Though seldom treated as informative predictive diagnostic biomarkers, the expression levels of heat shock proteins are useful prognostic biomarkers for tumorigenesis in some cancers (38,39). For example, the expression level of HSP27 is associated with a poor prognosis in gastric, liver, and prostate carcinomas (40)(41)(42). It has also been shown that HSP105 is one of the most highly upregulated proteins in melanoma and colon cancer patients, an upregulation that is correlated with hyperactivation of Wnt signaling (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced expression of Hsp27 has been associated with poor prognosis in several tumor types (e.g., gastric [12,13], liver [14] and prostate carcinoma [15]), but good prognosis in others (endometrial adenocarcinomas [16,17] and oesophageal cancer [18,19]). Several proteomic studies identified Hsp27 as a highly over-expressed protein in OSCC [20,21].…”
Section: Introductionmentioning
confidence: 99%